Sistem Pelayanan Customer Service dan Tiket Checkin PT KAI DAOP 8 Surabaya di Stasiun Gubeng - Nirawati, Lia; Aras, Aisyah Rachmayanti (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2024)
Railway transportation is considered an efficient mode of transportation in Java Island because it can transport passengers and goods quickly and in large quantities. Regarded as a highly popular mode of transportation, PT KAI (Persero) is committed to providing the best service with the tagline "Adaptive, Solution-oriented, Collaborative for Indonesia", offering quality services and comfort, and improving customer service and ticketing systems. This research focuses on services and ticket sales relevant to PT KAI's needs and interests. The analytical method includes observing operational processes and learning about company policies. Data collection involves interviews with relevant personnel, internal and external data analysis, and direct observation of processes at PT KAI. Subsequently, analysis and interpretation are conducted on the collected data, aiming to gain a deep understanding of emerging findings. The methods employed may include statistical analysis, modeling, and theoretical approaches to support conclusions.